TAUJÎH AL-ÂYAT SEBAGAI ALTERNATIF MENYIKAPI POLEMIK NASAKH - Abdul Jalil (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
This article describes some of verses of the Qur’an in which by some Islamic scholars known as nâsikh-mansûkh (the abrogating and abrogated [verses]), although naskh (abrogation) itself still leaves some weaknesses either from conceptional side or operational side, the polemic relating to naskh (abrogation) is still lively discussed. The focus of the study was on how to offer alternative solutions in responding nasakh, so that it does not fall into the problem of pros and cons regarding nasakh. This research is a library research with descriptive-comparative-analytical method and normative-philosophical approach. The conclusion of the study shows that the deletion of verse with another verse that clearly describes about the Allah’s saying should be free from taghyîr (conversion) and tabdîl (alteration), even though there is a dalil (evidence) that can be used as a hujjah (logical reason) that naskh can happen. It does not mean abrogating the verse of the Qur’an, but it is the earlier sharia (Islamic law) that will be abrogated, then enacted the sharia of prophet Mohammad. A claim of contradiction found in the verses of Qur’an is actually created from thoughts and point of view of each ulama’ (Islamic scholars), not from the text itself. Therefore, selecting and using alternative ways in understanding a verse that seems to contradict each other, such as using verse conciliation and taujîh al-ayat (verse orientation) based on its place is an inevitability to avoid polemic of naskh (abrogation)